THE USE SCRAMBLE MODEL IN STUDENTS’ ABILITY OF NARRATIVE TEXT WRITING AT CLASS XI SMA NEGERI 2 LAWE BULAN ACADEMIC YEAR 2021/2022 - Hajrah Yusmaini; Abdul Halim (STKIP USMAN SAFRI KUTACANE, 2023)
This study deals with the use of scramble model in students’ ability of narrative text at class XI in SMA Negeri 2 Lawe Bulan Academic Year 2021/2022. Its objective is to find out whether the use scramble model has a significance effect in narrative text writing. Population and samples used in this study were all students of class X total 36 students. The method used in this study is an experimental method with a one group as pretest and posttest design .This study was carried on using quantitave method. The data was analysed by using t-test. The researcher found the pretest mean = 43,05 , deviation standard = 4,48 and experienced an increase in the posttest mean = 80,83 , deviation standart = 4,55. From this analysis, writer found that guided scramble model has significane in teaching writing narrative text. It can be proved by the result of the analysis showed that “ ” observed about 35,64 was higher than “ttable” about 2,030 with the level significance is 0,05% it implies that the teacher of English should use scramble model in teaching narrative text writing so that the teaching and learning process can be successful.